HIV Testing Policies in Florida - Jennifer Syvertsen; Hilda Leon; Jeffrey Beal; Marlene LaLota; Sherry Riley; Michael D. Knox (University of North Florida, 2009)
To combat the HIV/AIDS epidemic, strong policies that promote HIV testing are a primary mechanism for helping public health officials to understand the populations at risk, informing prevention initiatives, and linking infected individuals to the timely care they need. This paper describes HIV testing policies with the goal of improving early diagnosis and treatment of Floridians.